Digital Marketing Training and Assistance for MSMEs at INS Kayu Tanam High School: Pelatihan Dan Pendampingan Digital Marketing Bagi UMKM Di SMA INS Kayu Tanam - Aggy Pramana Gusman; Hasri Awal (KPN Kopertis X, 2023)
Technological developments have created many opportunities for many sectors. One of them is the opportunity for students to start becoming MSME actors. A business that utilizes technological media has a great opportunity to develop. Utilizing technology in a business can be done with digital-based marketing or what is usually called digital marketing. Digital marketing is an online promotional and marketing activity by utilizing social media, e-commerce and other digital platforms. This research focuses on digital marketing assistance and training for MSMEs at SMA Ins Kayu Tanam, Padang City This research aims to identify and analyze the implementation of digital marketing in promotional and marketing activities carried out by MSME students at SMA Ins Kayu Tanam. The method used in this research is descriptive qualitative using observation techniques and focused discussions in collecting data. Based on the research results, the implementation of digital marketing at Ins Kayu Tanam High School has gone well, but there are still obstacles faced, namely that there are still some MSME players who lack understanding of technology